The Inhibition of Caspase-1- Does Not Revert Particulate Matter (PM)-Induced Lung Immunesuppression in Mice - Colarusso, Chiara; De Falco, Gianluigi; Terlizzi, Michela; Roviezzo, Fiorentina; Cerqua, Ida; Sirignano, Mariano; Cirino, Giuseppe; Aquino, Rita P.; Pinto, Aldo; D'Anna, Andrea; Sorrentino, Rosalinda (Frontiers in Immunology, 2019)
Background. Air pollution is becoming a threatening issue for human health. Many epidemiological studies relate air pollution index to adverse effects in terms of disease incidence and/or disease exacerbation. In our previous studies, we found air pollutants can induce the release of pro-inflammatory cytokines from human peripheral blood cells. To better understand, the effects of air pollution on the lung, we took advantage of an animal model. Experimental Approach. Mice were intratracheally and daily exposed to urban collected particulate matter (PM, PM10 and PM1) and to the sub-micrometric carbonaceous component, Soot. Results. We found that PM10, PM1 and Soot promoted lung inflammation associated to higher bronchial responsiveness and lower dilation together with an immunosuppressive lung environment, characterized by tolerogenic dendritic cells (DCs), macrophages and myeloid -derived suppressor cells (MDSCs), the latter two Arginase I positive. In support, higher recruitment of Treg associated to higher levels of IL-10 were detected in the lung of PM10, PM1 and Soot treated mice. This effect was not abolished by the administration of a caspase-1 inhibitor, Ac-Y-VAD, implying that the canonical inflammasome complex was not associated to PMx-induced lung immunosuppression in mice. Conclusion. Our study proves that PM exposure leads to an immunosuppressive lung environment in a caspase-1-independent manner, paving the way to understand the molecular and cellular mechanism/s underlying the establishment of some respiratory disorders according to the exposure to air pollution.